GC-MS (Gas Chromatography-Mass Spectrometry) Metabolit Sekunder Ekstrak Etanol dan Metanol Daun Kirinyuh (Chromolaena odorata L.) - Florian Mayesti Prima Remba Makin; Ite Morina Yostianti Tnunay; Gede Arya Wiguna (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Kirinyuh (Chromolaena odorata L.) is a woody shrub plant that can grow quickly so it is an aggressive competitor. Traditionally, kirinyuh leaves have been used as a wound healing medicine, treating sore throat, malaria, headache, anti-diarrheal, astringent, antiplasmodial, antihypertensive, and antiinflammatory. This study aims to determine the content of secondary metabolites of kirinyuh leaves using ethanol and methanol solvents. This type of research is qualitative research. The results showed that the ethanol solvent displayed 1 peak with the possibility of 3 secondary metabolites with a concentration of 100%, namely Germacrene D $$ 1,6-Cyclodecadiene, 1-methyl-5-methylene-8-(1-methylethyl)-, [s-(E,E)]- (CAS) Germacra-1(10),4(15),5-triene, (-)- (CAS) (-)-Germacrene D $$; Alpha.-Amorphene $$ .ALPHA. AMORPHENE $$ Naphthalene, 1,2,4a,5,6,8a-hexahydro-4,7-dimethyl-1-(1-methylethyl)-, [1S-(1.alpha.,4a.beta.,8a.beta.)]- (CAS) 6.alpha.-Cadina-4,9-diene, (-)- (CAS) 6.alpha.-Cadina-4,9-diene $$ .alpha.-Amorphene, (-)- $$ (-)-.alpha.-Amorphene $$, and Calarene $$ 1H-Cyclopropa[a]naphthalene, 1a,2,3,5,6,7,7a,7b-octahydro-1,1,7,7a-tetramethyl-, [1aR (1a.alpha.,7.alpha.,7a.alpha.,7b.alpha.)]- (CAS) .beta.-Gurjunene $$ 1(10)-Aristolene, (+)- $$ .delta.1(10)-Aristolene $$ 1H Cyclopropa[a]naphthalene, 1a,2,3,5,6,7,7a,7b-octahydro-1,1,7,7a-tetramethyl-, (1aR,7R,7aR,7bS)-(+)- $$ BETA-GURJUNENE $$ (+)-Calarene $$ (+)-.DELTA.1(10)-Aristolene $$ (+)-1(10)-Aristolene $$. Methanol solvent produces 3 peaks, number 3 is the highest peak with a concentration of 77.31% with the possibility of 5 compounds namely Iron, (.eta.5-2,4-cyclopentadien-1-yl)[(1,2,3,3a,7a-.eta.)-4,5,6,7-tetrahydro-4-hydroxy-5-methyl-1H-inden-1-yl]-, stereoisomer (CAS); 2,4-diphenyl-2-hydroxymethylpyrano[2,3-b][1]benzopyran-5-one $$ 2H,5H-Pyrano[2,3-b][1]benzopyran-5-one, 3,4-dihydro-2-(hydroxymethyl)-2,4-diphenyl- (CAS); Kauran-18-oic acid, 7-(acetyloxy)-15,16-epoxy-, methyl ester, (4.alpha.,7.beta.,15.alpha.)- (CAS) METHYL 7.BETA.-ACETOXY-15,16 .ALPHA.-EPOXY-16.BETA.-(-)-KAURAN-18-OATE $$; Stannane, tetrakis(1-methylethyl)- (CAS) Tetraisopropyltin $$ Tetraisopropylstannane $$ Stannane, tetraisopropyl- $$ (iso-C3H7)4Sn $$ tetra-i-Propyltin $$; and Cholest-5-en-3-ol (3.beta.)- (CAS) Lanol $$ Dythol $$ Kathro $$ Dusoran $$ Cordulan $$ Dusoline $$ Hydrocerin $$ Cholesterin $$ Cholesterol $$ Tegolan $$ (-)-Cholesterol $$ Provitamin D $$ Cholesterol base H $$ Wool alcohols B. P. $$ Cholesteryl alcohol $$ Cholest-5-en-3.beta.-ol $$ Nimco cholesterol base H $$ 5:6-Cholesten-3.beta.-ol $$ 3.beta.-Hydroxycholest-5-ene $$ Cholest-5-en-3-ol, (3.beta.)- $$ Nimco cholesterol base No. 712 $$ .DELTA.5-Cholesten-3.beta.-ol $$ 5-Cholesten-3.beta.-ol $$ Cholestrin $$. The contents of the secondary metabolites of kirinyuh leaves extracted from ethanol and methanol solvents have different types, amounts, and compositions.